El‐Hattab‐Alkuraya syndrome caused by biallelic WDR45B pathogenic variants: Further delineation of the phenotype and genotype. Issue 5 (12th April 2022) - Almannai, Mohammed; Marafi, Dana; Abdel‐Salam, Ghada M. H.; Zaki, Maha S.; Duan, Ruizhi; Calame, Daniel; Herman, Isabella; Levesque, Felix; Elbendary, Hasnaa M.; Hegazy, Ibrahim; Chung, Wendy K.; Kavus, Haluk; et al.
Abstract: Homozygous pathogenic variants in WDR45B were first identified in six subjects from three unrelated families with global development delay, refractory seizures, spastic quadriplegia, and brain malformations. Since the initial report in 2018, no further cases have been described. In this report, we present 12 additional individuals from seven unrelated families and their clinical, radiological, and molecular findings. Six different variants in WDR45B were identified, five of which are novel. Microcephaly and global developmental delay were observed in all subjects, and seizures and spastic quadriplegia in most. Common findings on brain imaging include cerebral atrophy, ex vacuo ventricular dilatation, brainstem volume loss, and symmetric under‐opercularization. El‐Hattab‐Alkuraya syndrome is associated with a consistent phenotype characterized by early onset cerebral atrophy resulting in microcephaly, developmental delay, spastic quadriplegia, and seizures. The phenotype appears to be more severe among individuals with loss‐of‐function variants whereas those with missense variants were less severely affected suggesting a potential genotype–phenotype correlation in this disorder. A brain imaging pattern emerges which is consistent among individuals with loss‐of‐function variants and could potentially alert the neuroradiologists or clinician to consider WDR45B ‐related El‐Hattab‐Alkuraya syndrome. Abstract : Neuroimaging criteria that could potentially suggest El‐Hattab‐Alkuraya syndrome: (1) Cerebral atrophy disproportionately most prominent in frontal lobes. (2) Ex vacuo ventricular dilatation with notable posterior‐horn predominance. (3) Brainstem volume loss with flattening of belly of the pons. (4) Symmetric under‐opercularization.